Supervision and Professional Development in Social Work Practice - Nickson, A M; Carter, Margaret-Anne; Francis, Abraham P. (Thousand Oaks : SAGE Publishing, 2020)
"Supervision and Professional Development in Social Work Practice aims to familiarize its readers with the current state of supervision in social work, provide them a common platform for reflection and action and thereby promote excellence in their respective learning, research and professional practice areas. It incorporates contributions by scholars, practitioners and students from various backgrounds, professional disciplines and countries. The ideas, concepts and practice frameworks discussed in this book are useful in any human service context. However, they need to be adapted with cultural sensitivity and appropriate levels of consultation and guidance to effectively challenge prevalent practice frameworks and support the embracing of new ideas to enhance professional and authentic engagement. The book utilizes several research studies, views, experiences and reflections, and includes numerous Voices from the Field, which provide diverse perspectives and viewpoints as well as practical help. This book will prove indispensable for academicians, practitioners, supervisors and supervisees as well as postgraduate and advanced undergraduate students of social work, counselling, psychology and education. Amanda M. Nickson runs her own business, Interactive Solutions, specializing in training, supervision and organizational consultancy in Townsville, Australia. Margaret-Anne Carter is National Chair for Counselling with the Australian College of Applied Psychology, Brisbane, Australia. Abraham P. Francis is Associate Professor in Social Work and Human Services at James Cook University, Townsville, Australia"--
Keywords: Social work education -- Social work education -- Social service--Practice